Resistant rootstocks mitigate ionic toxicity with beneficial effects for growth and photosynthesis in grapevine grafted plants under salinity - Amorim, Thialla Larangeira; Santos, Hugo Rafael Bentzen; Neto, Juracy Barroso; Hermínio, Pedro José; Silva, José Raliuson Inácio; Silva, Marcela Maria Albuquerque; Simões, Adriano Nascimento; Souza, Eduardo; Ferreira-Silva, Sérgio Luiz (Scientia horticulturae, 2023)
•The Na+ exclude trait from shoot is associate to salt-resistance in vine rootstocks.•Salt-sensibility of 1103P and SO4 rootstocks occurred with a higher Na+ levels.•Lower Na+ level was associate to salt-resistance of IAC 313 and IAC 572 rootstocks.•The higher K+/Na+ ratio was associated with salt-resistance in IAC 313 and IAC 572.•The grafted plants on the IAC 313 and IAC 572 rootstocks were more salt-resistance. The identification of salt-tolerant rootstocks can be an important strategy for producing vines in salt-affected areas. In this study, was tested the hypothesis that resistant rootstocks can mitigate the salinity damages by the lower ionic toxicity associated to best growth and photosynthesis in grapevine grafted plants. The four grapevine (Vitis spp.) rootstocks (‘IAC 313,’ ‘IAC 572,’ ‘SO4’ and ‘1103P’) and the grafted plants of ‘BRS Vitória’ variety on these rootstocks were exposed to increase NaCl (0, 40 and 80 mM NaCl) for the salt treatments. Under salinity, ‘IAC 313′ and ‘IAC 572′ rootstocks showed lower Na+content and higher K+ levels in leaves relative to other rootstocks. This response was associated with a higher leaf K+/Na+ ratio in the grafted and nongrafted plants of the ‘IAC 313′ and ‘IAC 572′ rootstocks. Based on the root and leaf dry weight (DW), the growth of the ‘IAC 313′ rootstock was unaffected by salinity, while ‘IAC 572′ showed a lower loss of DW relative to 1103P and SO4 rootstocks. All four rootstocks experienced increased membrane damage under saline conditions, but lipid peroxidation was lower in the ‘IAC 313′ rootstock. Grape plants grafted with the ‘BRS Vitória’ variety onto the IAC rootstocks (Vit/IAC 313 and Vit/IAC 572) presented higher efficiency of gas exchange and electron flow under salt stress, traits that were influenced by the rootstock genotype. Photochemical quenching (qP) and the electron transport rate (ETR) decreased under saline conditions, a response that was more intensive in Vit/1103P plants. In summary, our data showed that among evaluated rootstocks the ‘IAC 313′ and ‘IAC 572′ are better acclimated to salt and can be considered for vine production in salt-affected areas.